Pengaruh Penambahan Serat Baja Terhadap Kuat Tekan Beton Pada Berbagai Tingkat Kepadatan - Gea, Popi Marjaya; Dohare, Gofu Aro; Zebua, Mey Kristo; Zebua, Ayub Kristianto; Zebua, Dermawan; Ndruru, Rointus Juang (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
This study aims to examine the effect of steel fiber addition on the compressive strength of concrete at various density levels. Concrete is a commonly used construction material but has weaknesses in withstanding high compressive loads. To improve the mechanical properties of concrete, one method used is the addition of steel fibers into the concrete mix. In this study, steel fibers were added at different volume variations, and the concrete was tested at different density levels. The test results showed that the addition of steel fibers can increase the compressive strength of concrete, with a more significant effect at higher density levels. The addition of steel fibers also improved load distribution within the concrete and reduced the potential for cracking, thus enhancing the overall performance of the concrete